Machine learning, optimization, and data science : 4th International Conference, LOD 2018, Volterra, Italy, September 13-16, 2018, Revised selected papers /: 4th International Conference, LOD 2018, Volterra, Italy, September 13-16, 2018, Revised selected papers. (2019) - Unknown
No abstract available